SAT0317 Tofacitinib in patients with psoriatic arthritis and metabolic syndrome: a post-hoc analysis of phase 3 studies. (12th June 2018) - Ritchlin, C.; Giles, J.; Ogdie, A.; Gomez-Reino, J.; Stockert, L.; Young, P.; Wang, C.; Romero, A.B.; Kudlacz, E.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA). PsA is often associated with comorbid metabolic syndrome (MetS), which is linked to increased inflammation and severity of underlying PsA, and higher cardiovascular risk. 1, 2 Patients (pts) with PsA and comorbid MetS frequently demonstrate decreased therapeutic responses and lower probability of achieving minimal disease activity. 3, 4 Objectives: To compare key efficacy and safety endpoints in tofacitinib-treated pts with PsA and MetS in Phase (P) 3 studies. Methods: Two double-blind P3 studies enrolled pts with active PsA who either had an inadequate response (IR) to ≥1 conventional synthetic (cs)DMARD and were TNFi-naïve (OPAL Broaden; n=422; 12 months; NCT01877668 ) or IR to ≥1 TNFi (OPAL Beyond; n=395; 6 months; NCT01882439 ). Pts were randomised to receive tofacitinib 5 mg BID, tofacitinib 10 mg BID, adalimumab 40 mg Q2W (OPAL Broaden only) or placebo (PBO); all pts continued on a single, stable csDMARD. In this analysis, data for tofacitinib- and PBO-treated pts were pooled from both studies; efficacy and safety endpoints at Month (M) 3 were descriptively reported according to the presence or absence of MetS at baseline (defined as ≥3 of the following: hypertension, elevated triglycerides, reduced HDL cholesterol, large waist size and elevated fasting glucose levels 5 ). Efficacy endpoints included: ACR20 response; change from baseline in HAQ-DI; PASI75 response; and changes from baseline in Pt's Global Assessment of Arthritis and C-reactive protein (CRP). Safety endpoints included: treatment-emergent adverse events (AEs); fasting lipid levels (LDL, HDL and total cholesterol, and triglycerides). Results: This analysis included 294 pts with MetS (tofacitinib 5 mg, n=99; 10 mg, n=101; PBO, n=94) and 416 pts without (tofacitinib 5 mg, n=139; 10 mg, n=135; PBO, n=142). At baseline, pts with MetS had a higher mean age (53.2 vs 46.2 years) and mean BMI (33.2 vs 27.3 kg/m 2 ), and a greater proportion of pts with MetS had a CRP level >2.87 mg/L (upper limit of normal) (67.7 vs 58.9%) and were taking lipid-lowering medications (Day 1: 26.5 vs 3.8%). Tofacitinib efficacy was generally similar in pts with and without MetS (Table). LDL, HDL and total cholesterol, and triglyceride levels generally increased from baseline to M3 (Table). Among pts with MetS, AEs occurred in 55.6% treated with tofacitinib 5 mg (serious AEs [SAEs], 2%) and in 42.6% treated with tofacitinib 10 mg (SAEs, 2%). Among those without MetS, AEs occurred in 42.4% treated with tofacitinib 5 mg (SAEs, 1.4%) and in 54.8% treated with tofacitinib 10 mg (SAEs, 1.5%). Conclusions: Across 2 P3 studies, tofacitinib showed generally similar efficacy and safety in pts with PsA with or without MetS. References: [1] Haroon M, et al. J Rheumatol2014; 41:1357–65. [2] Haroon M, et al. J Rheumatol2016;43:463–4. [3] Stober C, et al. Rheumatology2018;57:158–63. [4] Costa L, et al. Immunol Res2015;61(1–2):147–53. [5] Alberti KG, et al. Circulation2009;120:1640–5. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by S Piggott of CMC and funded by Pfizer Inc. Disclosure of Interest: C. Ritchlin Grant/research support from: AbbVie, Amgen and UCB, Consultant for: AbbVie, Amgen, Celgene, Janssen, Novartis, Pfizer Inc, Sun and UCB, J. Giles: None declared, A. Ogdie Grant/research support from: Novartis, Consultant for: Novartis, Pfizer Inc and Takeda, J. Gomez-Reino Grant/research support from: AbbVie, MSD, Pfizer Inc and Roche, Consultant for: Pfizer Inc, Speakers bureau: AbbVie, Biogen, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc and Roche, L. Stockert Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, P. Young Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. B. Romero Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc